2021
DOI: 10.3389/fpls.2021.740923
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Structures Forming the Lignin-Like Fractions of Ancestral Plants

Abstract: In the present work, lignin-like fractions were isolated from several ancestral plants –including moss (Hypnum cupressiforme and Polytrichum commune), lycophyte (Selaginella kraussiana), horsetail (Equisetum palustre), fern (Nephrolepis cordifolia and Pteridium aquilinum), cycad (Cycas revoluta), and gnetophyte (Ephedra fragilis) species– and structurally characterized by pyrolysis-gas chromatography-mass spectrometry (Py-GC/MS) and two-dimensional nuclear magnetic resonance (2D-NMR) spectroscopy. Py-GC/MS yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…It is worth noting that the detection of the oligomers presented in Figure 3 can also shed light on the nature of lignin-like biopolymers in P. commune , which have been previously reported in the literature [ 15 , 16 ]. It can be assumed that the acetone extraction used in our study made it possible to extract only a low molecular weight fraction of the polymeric dihydrochalcone synthesized by the plant by analogy with algal phlorotannins [ 23 ] with the formation of fucol-type aryl–aryl bonds.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…It is worth noting that the detection of the oligomers presented in Figure 3 can also shed light on the nature of lignin-like biopolymers in P. commune , which have been previously reported in the literature [ 15 , 16 ]. It can be assumed that the acetone extraction used in our study made it possible to extract only a low molecular weight fraction of the polymeric dihydrochalcone synthesized by the plant by analogy with algal phlorotannins [ 23 ] with the formation of fucol-type aryl–aryl bonds.…”
Section: Resultssupporting
confidence: 60%
“…However, Karmanov et al reported lignin isolation from P. commune that was similar to softwood lignins in many characteristics [ 15 ]. The most recent study by Rencoret et al [ 16 ] points to the detection of weak signals belonging to the p -hydroxyphenyl structures typical for lignin in the NMR spectra of a lignin-like substance isolated from P. commune . However, it was noted that flavonoids or other polyphenolic compounds can also be their source.…”
Section: Introductionmentioning
confidence: 99%
“…The observation of the formation of ligninlike polymers in the oxidation of CA using a mushroom laccase was the first demonstration of the nature of lignin as a dehydrogenation polymer derived from monolignols . Furthermore, the occurrences of numerous lignin substructures, including tetrahydrofuran β–β structures from acylated monolignols, benzodioxane structures from catechol-type monolignols, lignin-integrated flavonoids, , and various new lignin substructures produced in transgenic plants, have been elucidated by the in vitro dehydrogenative polymerization of various lignin monomers.…”
Section: Introductionmentioning
confidence: 99%
“…previous studies, most of the biochemical and genetic pre-requisites for the evolution of true lignin and other derivatives of the general phenylpropanoid pathway were already present in the common ancestor of land plants (Weng and Chapple, 2010;Espiñeira et al, 2011;Renault et al, 2019;Kriegshauser et al, 2021;Rencoret et al, 2021). Our previous results (Kruse et al, 2022) also suggested that the ability to produce caffeoylquinatethe hydroxycinnamoyl CoA quinate transferase (HQT) activityexists in charophytic algae and likely existed in the ancestor of land plants.…”
Section: Clade-specific Expansions and Duplication-divergence Charact...mentioning
confidence: 79%